Poverty and the transition to adulthood: risky situations and risky events - Arnstein Aassve; Maria A. Davia; Maria Iacovou; Letizia Mencarini (University of Essex, Institute for Social and Economic Research (ISER), 2005)
This paper analyses the factors associated with poverty among young people across 13 countries of the pre-enlargement European Union, and examines how these factors differ between countries. Previous research has shown that young people in most European countries face a higher-than-average risk of poverty; this is to be expected, since young adulthood is a time when people undergo rapid transitions in multiple spheres (education; the labour market; the family), many of which may pre-dispose the young person to poverty. Here, we use data from the European Community Household Panel (ECHP), making use of random effects models and discrete time hazard regressions to examine the role of several factors on a young persons probability of being poor; and on his or her probability of entering and exiting poverty. We also carry out parallel analysis using measures of non-monetary deprivation. Our results show that while many factors are correlated with young peoples risks of poverty or deprivation, the largest risk factor by far is moving out of the parental home.
Keywords: 330